Primary school students' attitudes towards physical culture, physical education lessons and exercises during a pandemic - Adrian Gądek (University of Applied Sciences in Tarnow, Poland, 2020)
Introduction: One of the main goals of physical education is forming students' proper attitudes towards physical exercises and culture. The study aimed to determine primary school students' attitudes towards physical culture, physical education lessons and physical activity. Material and methods: The tests were conducted at the turn of May and June 2020 among primary school students from Kraków and Tarnów. They comprised 336 students, including 141 girls. Research employed the Questionnaire for testing attitudes of the youth towards physical culture by S. Strzyżewski (Pol. Kwestionariusz do badania postaw młodzieży wobec kultury fizycznej). Results: The test results demonstrated students' positive attitudes towards physical culture. For most of the examined (76.2%) physical activity means pleasure. More than a half of the students (57.7%) are satisfied with physical education classes. Boys enjoyed physical exercises more frequently than girls. Conclusions: Students present a positive attitude towards physical culture, physical education lessons and physical activity. The level of attitudes is higher among boys than girls. It would be advisable to make physical education lessons more attractive to girls in order to form positive attitudes.